2022
DOI: 10.1155/2022/1482811
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome and Plasma Metabolomic Analysis in Patients with Myelodysplastic Syndrome

Abstract: Myelodysplastic syndrome (MDS) is a heterogeneous group of clonal hematopoietic stem cell disorders. Studies have shown the involvement of an abnormal immune system in MDS pathogenesis. The gut microbiota are known to influence host immunity and metabolism, thereby contributing to the development of hematopoietic diseases. In this study, we performed gut microbiome and plasma metabolomic analyses in patients with MDS and healthy controls. We found that patients with MDS had a different gut microbial compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…The relative abundance of these 2 potential pathogens was higher in summer (Table 1). Streptococcus luteciae can cause infectious diseases and colitis‐associated colorectal cancer in animals or humans (Liang et al 2014, Jiang et al 2022; Table ). Clostridium perfringens can lead to neurological lesions and enteritis in animals or humans (Uzal and Kelly 1998, Uzal et al 2002, Kiu and Hall 2018; Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of these 2 potential pathogens was higher in summer (Table 1). Streptococcus luteciae can cause infectious diseases and colitis‐associated colorectal cancer in animals or humans (Liang et al 2014, Jiang et al 2022; Table ). Clostridium perfringens can lead to neurological lesions and enteritis in animals or humans (Uzal and Kelly 1998, Uzal et al 2002, Kiu and Hall 2018; Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Their ndings revealed that Prevotella heparinolytica stimulated the differentiation of Th17 cells that colonize the intestinal tract of VK*MYC mice and subsequently enter the BM of transgenic mice, thereby expediting the progression of MM. At the same time, several clinical studies found the GM of patients with hematologic malignancies exhibit dysbiosis compared with healthy individuals (Jiang et al, 2022;Zhang et al, 2019). The dysbiosis of GM has the potential to induce alterations in GM-derived metabolites, which act as signaling molecules and substrates for immune and metabolic responses.…”
Section: Introductionmentioning
confidence: 99%
“…Their ndings revealed that Prevotella heparinolytica stimulated the differentiation of Th17 cells that colonize the intestinal tract of VK*MYC mice and subsequently enter the BM of transgenic mice, thereby expediting the progression of MM. At the same time, several clinical studies found the GM of patients with hematologic malignancies exhibit dysbiosis compared with healthy individuals [10,11]. The dysbiosis of GM has the potential to induce alterations in GM-derived metabolites, which act as signaling molecules and substrates for immune and metabolic responses.…”
Section: Introductionmentioning
confidence: 99%